High thermal stability and low power dissipation PCM with nanoscale oxygen‐doped SS thin film. Issue 8 (3rd September 2018) - You, Haipeng; Hu, Yifeng; Lai, Tianshu; Chou, Qingqian; Zhu, Xiaoqin; Zou, Hua
Abstract : To improve thermal stability and reduce power dissipation of phase‐change memory (PCM), the oxygen‐doped Sn15 Sb85 (SS) thin film is proposed by magnetron sputtering in this study. Comparing to undoped Sn15Sb85(SS), the oxygen‐doped‐SS thin film has superior thermal stability and better data retention. Meanwhile, the electrical conductivity of crystallisation oxygen‐doped‐SS thin film is also lower than that of SS, which means its less power consuming in PCM. The electrical conductivity ratio between amorphous and crystalline states for oxygen‐doped SS reaches up to two orders of magnitude. After oxygen doping, the root‐mean‐square surface roughness from amorphous (0.29 nm) to crystalline (0.46 nm) state for oxygen‐doped‐SS thin films becomes smaller. The switching time of amorphisation process for the oxygen‐doped‐SS thin film (∼2.07 ns) is shorter than Ge2 Sb2 Te5 (GST) (∼3.05 ns). X‐ray diffractometer is recorded to investigate the change of crystalline structure. Thus, the authors infer that oxygen‐doped SS is a promising phase‐change thin film for PCM.